Impacto da estratégia saúde da família com equipe de saúde bucal sobre indicadores de saúde bucal: análise em municípios do nordeste com mais de 100 mil habitantes - Pereira, Carmen Regina dos Santos (2010)
This study examined in municipalities of Northeast of Brazil with more than one hundred thousand people who incorporation of Oral Health Teams (OHT) into the Family Health Strategy (FHE) the possible impact on oral health indicators. Sought to answer whether implementation OHT brought the best indicators of health problems and coverage, compared to areas without coverage by the FHE through a community trial in parallel, quasi-randomized. In each of the municipalities surveyed were 20 census tracts, 10 were located in areas covered by oral health teams in the ESF and 10 industries in areas not covered. The final sample consisted of 59.221 individuals. We compared oral health indicators related to health problems, access to services and coverage of oral health actions. The analysis strategy was based on the calculation of prevalence ratios and confidence intervals, adjusted for confounding factors through Poisson regression with robust variance. It also has measured the association between an indicator of social inequality for comparison between areas. The best results are associated with indicators of access and coverage of oral health actions at the expense of the indicators of health problems, suggesting a possible maintenance of a traditional model of practice yet. The results also suggest a possible effect of a specific policy in the area of primary care on inequality in access. From the discussions presented throughout this work, we can see that the impact analysis of public policy, obtained by comparing areas with and without the intervention, not only captures the effect on the target population, but other dimensions of organization service and therefore should be understood as one of the analytical possibilities related to the management